Implementation of wideband digital transmitting beamformer based on LFM waveforms. Issue 2 (1st April 2017) - Fu, Wei; Jiang, Defu; Su, Yu; Qian, Rong; Gao, Yang
Abstract : A wideband digital transmitting beamformer based on linear frequency modulation (LFM) signals is presented in this study. The wideband beamformer is realised as a combination of direct digital synthesisers and fractional delay (FD) filters in polyphase structure. By using coordinate rotation digital computer algorithm, high intermediate frequency wideband LFM signal is generated and phase compensation for beamforming is accomplished in field programmable gate array. The impact of different number of quantisation bits on signal generation is analysed. The results of waveform generation and FD filter design are given. At last, the transmitting beam pattern is simulated.